Analysis on Economic Factors Affecting Corporate Social Responsibility in Private Organizations; Case Study: Private Organizations in West Azerbaijan Province - Haghi, Mahrokh Lotfollahi; Peikani, Mehraban Hadi; Etebarian, Akbar (International Review of Management and Marketing, 2017)
Businesses nowadays have perceived that social issues must be taken seriously. One major requirement for corporations to survive in the global world and acquire a larger market share along with competitive advantage toward a competitive economy is observing social responsibility in businesses. Developing countries, however, require further consideration of the basics needed for social responsibility and creation of necessary incentives to remove barriers and overcome challenges. Corporate social responsibility offers solutions to be used in the business environment and respond the expectations of the society in the fields of law, ethics, business and community for organizations have huge environmental, social and economic responsibility toward their employees, stockholders, clients, governments, suppliers and all other beneficiaries. Needless to say that individuals, groups, institutions and organizations feeling responsible toward their society and its crises and problems through doing their best to tackle them will decrease problems significantly and improve the quality of life. The present study is an applied research conducted through descriptive analytical method. The data for the study were collected via library studies and questionnaires in private organizations of West Azerbaijan province and the data collected were analyzed descriptively and analytically. Statistical population of the study included all 3011 private companies in West Azerbaijan province from among which 340 companies were selected randomly according to simple table or Krejcie and Morgan table as statistical sample. The data were collected via a valid and reliable questionnaire and were then analyzed using SPSS 22 computer application. Results from the study revealed that 5 factors of following economic procedures for employees, economic interaction strategies for suppliers, financial management and marketing for customers, using environment friendly production resources elaborated an overall 61.656% of the variance of the economic factors affecting corporate social responsibility. Keywords: Economic factors; corporate social responsibility; Private organizations JEL Classifications: C32; O13; O47